2016
DOI: 10.1177/1049731515625326
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Validating Chinese Language Mental Health Recovery Measures in Hong Kong

Abstract: Objectives: Promoting recovery in mental health services is hampered by a shortage of reliable and valid measures, particularly in Hong Kong. We seek to cross validate two Chinese language measures of recovery and one of recovery-promoting environments. Method: A cross-sectional survey of people recovering from early episode psychosis (n = 121) and family members (n = 49) was taken. Two recovery measures, the Mental Health Recovery Measure and the recovery subscale of the Peer Outcomes Protocol, and one measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
0
2
0
6
Order By: Relevance
“…After receiving permission from Dr O'Connell to conduct a translation of the RSA-R, we conducted a bibliographic review on the RSA-R instrument, and found cross-cultural adaptations and validations made by authors from other countries Ye et al, 2013;Zuaboni et al, 2015;Bola et al, 2016) and its use (Kidd et al, 2010(Kidd et al, , 2011Mak et al, 2017) in different contexts.…”
Section: Resultsmentioning
confidence: 99%
“…After receiving permission from Dr O'Connell to conduct a translation of the RSA-R, we conducted a bibliographic review on the RSA-R instrument, and found cross-cultural adaptations and validations made by authors from other countries Ye et al, 2013;Zuaboni et al, 2015;Bola et al, 2016) and its use (Kidd et al, 2010(Kidd et al, , 2011Mak et al, 2017) in different contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Esta estratégia foi repetida na maioria das adaptações transculturais do RSA feitas em outros países, especialmente nas versões de trabalhadores e usuários 10,15,33,34 . No processo de adaptação transcultural do RSA família realizados no Canadá e China, não se identificou envolvimento dos familiares no processo, apenas participação em responder o questionário 9,11 . O primeiro foi a dificuldade para que os participantes preenchessem, sem orientação, o instrumento, o que fez com que a versão brasileira do RSA-R família/Brasil fosse aplicada mediante entrevista.…”
Section: Discussionunclassified
“…Tal uso facilita reflexão sobre os pontos fortes, bem como as limitações dos serviços dentro deste enfoque 7 . Esta escala apresenta boas propriedades psicométricas, sendo comumente utilizada em avaliações dos serviços de saúde mental em outros países [8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Introductionunclassified
“…Esses itens indagam sobre a participação do usuário em instâncias de gestão e política dentro dos serviços de saúde mental e se a equipe responde aos interesses e preocupações do mesmo. Bola et al (2016), associaram essas perdas ao aspecto cultural, acreditando que, como a diversidade étnica e cultural em Hong Kong não é tão grande como nos Estados Unidos, essas questões podem não ser tão apropriadas na avaliação da orientação ao recovery em serviços de saúde mental em Hong Kong.…”
Section: A Família Como Um Ator Emunclassified